Surgical management of bisphosphonate-related osteonecrosis of the jaw stages II and III - Bodem, Jens; Schaal, Carolin; Kargus, Steffen; Saure, Daniel; Mertens, Christian; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Oral surgery, oral medicine, oral pathology, oral radiology, and endodontology, 2016)
Objective - The value of surgery in advanced stages of bisphosphonate-related osteonecrosis of the jaw (BRONJ) is still controversial. Hence, we evaluated the effect of surgical therapy in BRONJ stages II and III in combination with a standardized perioperative adjuvant treatment. - Study Design - We included 39 patients who presented with BRONJ in a total of 47 locations and stages II (n = 23) and III (n = 24). All patients had exclusively received a monthly intravenous application of zoledronic acid. Surgical therapy consisted of complete removal of the necrotic jaw, accompanied by a standardized perioperative adjuvant treatment including intravenous antibiotic prophylaxis, gastric feeding, and an antimicrobiologic mouth rinsing. - Results - Overall, 35 (74.5%) of the 47 BRONJ sites were treated successfully, with success defined as complete mucosal healing of the exposed jaw (n = 24) or as relative healing when surgical therapy downscaled BRONJ II or III to asymptomatic BRONJ stage I (n = 11). Interestingly, perioperative adjuvant treatment or bisphosphonate therapy parameters showed no statistical effect on the treatment outcome. - Conclusions - The results of the present study prove the effectiveness of surgical therapy for BRONJ stage II or III.
Available online 1 December 2015
Gesehen am 11.02.2020